2014
DOI: 10.1080/07481187.2013.844747
|View full text |Cite
|
Sign up to set email alerts
|

Remarriage of War and Terror Widows: A Triadic Relationship

Abstract: The article focuses on the intimate relationships of remarried Israeli national widows. An analysis of interviews with 15 widows and 12 of their husbands demonstrated the widows' continuing connection to the deceased husband and thus gives further corroboration to the theory of "'continuing bonds'"; husbands also express their relationship as triadic, with the fallen husband assigned a unique position in the family constellation, albeit not threatening to the new husband. The article concludes with specific gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 12 publications
6
19
0
Order By: Relevance
“…Although our findings showed various ways of sharing grief with a variety of others, it is important to note that the second husband was the figure with whom the widow most often shared her grief. As such, our findings emphasize a pattern of shared grief which was also described by Bokek-Cohen (2014). Yet although other researchers have described the difficulties that bereaved parents (i.e., of a fallen soldier) have in uniting around other people's ways of commemorating familial grief (Malkinson & Bar-Tur, 2005), most of the military widows in this study described family members as being amenable to participating in their way of grieving.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although our findings showed various ways of sharing grief with a variety of others, it is important to note that the second husband was the figure with whom the widow most often shared her grief. As such, our findings emphasize a pattern of shared grief which was also described by Bokek-Cohen (2014). Yet although other researchers have described the difficulties that bereaved parents (i.e., of a fallen soldier) have in uniting around other people's ways of commemorating familial grief (Malkinson & Bar-Tur, 2005), most of the military widows in this study described family members as being amenable to participating in their way of grieving.…”
Section: Discussionsupporting
confidence: 71%
“…Various remarriage patterns have been described among young widows whose husbands died unexpectedly in a military context. Some studies have presented different ways of maintaining aspects of the first marriage within the second marriage, including a triadic relationship-that is, the wife, the dead husband, and the new husband (Bokek-Cohen, 2014). Alternatively, some studies have shown the creation of a whole new atmosphere in the second spousal relationship (Lebel, Lubish-Omer, & Pasik, 2015).…”
mentioning
confidence: 99%
“…Research in this field points to the uniqueness of the grieving process of parents compared with the grief of other family members, such as siblings and widows. Parents feel a deep and intense mourning that persists for a long period of time, whereas the mourning of siblings and widows decreases in intensity over time (Bokek-Cohen, 2014). Contrary to psychodynamic approaches, which hold that over time and in parallel with the mourning, a process of acceptance and resignation is established, recent studies emphasize that a successful outcome of mourning is not relinquishment and disengagement but rather renewed negotiation regarding the significance of the loss, its role, and its place (Leichtentritt et al, 2015).…”
Section: Elderly Bereaved Parents' Mourningmentioning
confidence: 99%
“…At a young age, the loss of a spouse takes place at a stage when the widow and the deceased husband are in the process of building their shared life. It leaves the widow with a physical emptiness, along with grief over life plans, shared dreams, and hopes that have been curtailed by the husband's death (Bokek-Cohen, 2014;Nuttman-Shwartz et al, 2019). Adapting to the loss of a partner is a dynamic, multidimensional process that involves elements of preserving the image of the partner who is no is deceased, together with the need to adapt to life without him.…”
Section: Mourning Of Widowsmentioning
confidence: 99%
See 1 more Smart Citation